A new archive of large volcanic events over the past millennium derived from reconstructed summer temperatures. (22nd August 2017) - Schneider, L; Smerdon, J E; Pretis, F; Hartl-Meier, C; Esper, J
Abstract: Information about past volcanic impact on climate is mostly derived from historic documentary data and sulfate depositions in polar ice sheets. Although these archives have provided important insights into the Earth's volcanic eruption history, the climate forcing and exact dating of many events is still vague. Here we apply a new method of break detection to the first millennium-length maximum latewood density reconstruction of Northern Hemisphere summer temperatures to develop an alternative record of large volcanic eruptions. The analysis returns fourteen outstanding cooling events, all of which agree well with recently developed volcanic forcing records from high-resolution bipolar ice cores. In some cases, however, the climatic impact detected with our new method peaks in neighboring years, likely due to either dating errors in the polar ice cores or uncertainty in the interpretation of atmospheric aerosol transport to polar ice core locations. The most apparent mismatches between forcing and cooling estimates occur in the 1450s and 1690s. Application of the algorithm to two additional and recently developed reconstructions that blend maximum latewood density and ring width data reproduces twelve of the detected events among which eight are retrieved in all three of the dendroclimatic reconstructions. Collectively, the new estimates of volcanic activity with precise age control provide independent evidence for forcing records during the last millennium. Evaluating the cooling magnitude in response to detected events yields an upper benchmark for the volcanic impact on climate. The average response to the ten major events in the density derived reconstruction is −0.60 °C ± 0.13 °C. Other last millennium temperature records from proxies and model simulations reveal higher cooling estimates, which is, to some degree, related to the very different high frequency variance in these timeseries.